Position of Land Deed Making Official (PPAT) in Bevoegdheid Bestuurs Perspective in Cirebon Regency - Eva Natalya Widyanarti (Sultan Agung Notary Law Review, 2020)
The research objective was to identify and describe: 1) Position of Land Deed Making Official (PPAT) in the perspective of Bevoegdheid Bestuurs. 2).The weaknesses of the position of the Land Deed Making Official (PPAT) from the perspective of Bevoegdheid Bestuurs. 3).The administrative responsibility of the Land Deed Making Official (PPAT) for deeds that are legally flawed from a Bevoegdheid Bestuurs perspective. The approach method used in this research is normative juridical.This type of research is classified as a descriptive analytical research. The data collection technique used literature study techniques, while the data analysis was descriptive qualitative analytical. The results show that 1. Basically the delegation of part of the authority to carry out land registration is one form of implementing the Bevoegdheid guidelines. Where the Bevoegdheid guideline referred to is the public authority or authority possessed by BPN as government. Thus it can be said that the PPAT obtained delegation authority from BPN. It is said to have obtained delegation authority because the position of BPN as a government agency is higher than that of PPAT. 2. Weaknesses arising from the position of PPAT in the perspective of Bevoegdheid bestuur is the occurrence of maladministration as a form of abuse of authority in making authentic deeds. 3. The form of PPAT administrative accountability for deeds with legal defects is divided into two areas. First, according to Article 62 PP No. 24 of 1997 is subject to sanctions in the form of: a) warning; b) Warning; c) Schorsing and d) Disrespectful termination of IPPAT membership. Second, Article 13 paragraph (1) Permen ATR No. 2 of 2018 regulates the development of the types of sanctions in PPAT into: a) written warning; b) temporary dismissal; c) honorific dismissal; and d) dishonorable discharge.